Calculation and design of self-excitation microwave devices in the S-parameters space - N. V. Zarjhetskaya; S. V. Savelkaev (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The technique of calculation of the microwave oscillator in the S-parameters space without external feedback and with parallel or serial external feedback of the active component (AC) is considered. The technique basis on the conditions of oscillator self-excitation, written in the complex form, and allows to calculate the complex AC loads reflection factors and the parameters of the external feedback providing the desired oscillation frequency and the maximum output power and approximately estimate the value of this power. Analysis of the АС stability and the self-excitation conditions ensures selection of the correct electrical circuit of the oscillator and the calculated AC loads complex reflection factors and the external feedback parameters ensures a synthesis of the considered oscillator topology.